Standard Specification for Pressure Vessel Plates, Alloy Steel, Chromium-Molybdenum (American Society of Testing Materials, 2006)
This specification covers chromium-molybdenum alloy steel plates intended primarily for welded boilers and pressure vessels designed for elevated temperature service.